Atmospheric neutrinos detected with the first KM3Net detection units of ARCA and ORCA - Coniglione, Rosa; Hofestädt, Jannik; Sinopoulou, Anna; Tzamariudaki, Ekaterini; Zaborov, Dmitry (Proceedings of Science, 2019)
KM3NeT is constructing two next-generation underwater Cherenkov detectors in the deep Mediterranean Sea. The ARCA detector is optimised for TeV-PeV neutrino astronomy, and the smaller and more-densely instrumented ORCA detector is optimised for oscillation research with few-GeV atmospheric neutrinos. The first detection units of both ARCA as well as ORCA have been deployed and are taking data. In this contribution, an analysis to detect atmospheric neutrinos in the first data of a single detection unit of ORCA and two detection units of ARCA is presented. With ORCA, a sample of 77 neutrino candidates in 125.3 days of livetime is extracted. A good agreement with expectations from Monte-Carlo simulations is found. With ARCA, 6 neutrino candidates are identified in 53.2 days of livetime.
CRIS-Team Scopus Importer:2021-04-20